2016
DOI: 10.1155/2016/1819209
|View full text |Cite
|
Sign up to set email alerts
|

Altered Mitochondrial Respiration and Other Features of Mitochondrial Function inParkin-Mutant Fibroblasts from Parkinson’s Disease Patients

Abstract: Mutations in the parkin gene are the most common cause of early-onset Parkinson's disease (PD). Parkin, an E3 ubiquitin ligase, is involved in respiratory chain function, mitophagy, and mitochondrial dynamics. Human cellular models with parkin null mutations are particularly valuable for investigating the mitochondrial functions of parkin. However, published results reporting on patient-derived parkin-mutant fibroblasts have been inconsistent. This study aimed to functionally compare parkin-mutant fibroblasts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
47
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 46 publications
11
47
1
Order By: Relevance
“…A few other studies, including our own, of PD patient iPSC-derived neurons with PARK2 mutation have also reported aberrant mitochondrial morphology and function (26,55,56), and several prior studies have addressed changes in energy metabolism associated with PD. The fall in ATP has been reported in different experimental PD models, such as MPTP mouse model (57) or skin fibroblasts isolated from PD patients (58).…”
Section: Discussionmentioning
confidence: 94%
“…A few other studies, including our own, of PD patient iPSC-derived neurons with PARK2 mutation have also reported aberrant mitochondrial morphology and function (26,55,56), and several prior studies have addressed changes in energy metabolism associated with PD. The fall in ATP has been reported in different experimental PD models, such as MPTP mouse model (57) or skin fibroblasts isolated from PD patients (58).…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, Pink1 mutant zebrafish show decreases in mitochondrial complex I and III activity [96] . Both parkin and PINK1 mutant patient cells, and cell/animal models have reduced mitochondrial respiration [93,[97][98][99] . Mitochondrial morphological abnormalities have also been reported in both parkin and PINK1 patient cells and models, however both elongation and fragmentation of the mitochondrial network has been observed.…”
Section: Parkin and Pink1mentioning
confidence: 99%
“…Clinical genotype–phenotype studies have shown that PD patients carrying a deletion of both exons 3 and 4 from PRKN have milder symptoms compared to patients with a parkin deficiency [ 11 , 12 ]. Such an explanation for the basis of disease variability in PD opens up new therapeutic strategies for Parkin-type ARJP by changing a severe disease phenotype into a milder form through redirecting PRKN pre-mRNA processing to induce an isoform missing exons 3 and 4.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, parkin function deficiency compromises its transcriptional repression of p53 and consequently mediates programmed neuronal cell death and neurodegeneration [ 9 , 10 ]. Genotype–phenotype studies on Parkin-type ARJP patients show that patients with genomic deletion of both exons 3 and 4 in PRKN present with milder symptoms than patients with the out-of-frame deletion of exons 3 or 4 alone [ 11 , 12 ]. These observations suggest that the parkin isoform missing domains encoded by exons 3 and 4 is semi-functional, and thus provides justification that inducing a PRKN mRNA isoform missing exons 3 and 4 may offer a therapeutic avenue for those ARJP patients with disease-causing mutations involving either exon 3 or 4.…”
Section: Introductionmentioning
confidence: 99%